Investigating of VLF signal persecutors for earthquake near Mentawai Island: article / Nurul Amirah Ahmad Kusaini - Ahmad Kusaini, Nurul Amirah (2014)
This paper investigate about SeismicIonosphere perturbation using Very Low Frequency (VLF) signal Observed in Malaysia. The propagation of VLF signals is between NWC transmitters and receiver at Selangor station. The length of the transmitter-receiver Great Circle Path (TRGCP) is 3000km. The propagation path of VLF signal identify the possible ionosphericperturbations related to the earthquake disaster occurred in Indonesia region within January 2009 – April 2011. Out of seven earthquakes detected within the period only one that show possible evidence is the earthquake at Mentawai Island on 25th October 2010. The magnitude is 7.7 and depth 20.6km. The data was analyzed using three methods (1) average nighttime and daytime amplitude variation (2) terminator time (TT and (3) nighttime fluctuation (NF) methods.